The determinants of customer loyalty in the sharing economy: a study of the largest local food delivery apps in Indonesia - Antonius Renaldi; Sri Rahayu Hijrah Hati; Ezlika Ghazali; Ujang Sumarwan; T. Ramayah (Cogent Business & Management, 2024)
The study examines the impact of customer-based value perception on customer loyalty with food delivery services applications provided by technology services companies in the sharing economy. The data were collected through an online survey from 310 customers of Gojek, Indonesia's largest food delivery services platform. This study shows that within the context of food delivery apps in the sharing economy, the value proposition design, value co-creation process, and value capture mechanism collectively play crucial roles in establishing the three types of customers' perceived value – perceived quality value, perceived price value, and perceived emotional value. Furthermore, the research demonstrates that both emotional and price values significantly impact customer loyalty to the food delivery services app. In contrast, the influence of quality value on loyalty is insignificant. The results indicate that it is essential for all culinary sellers or restaurateurs to consider partnering with the best multiservice platform provider company, that provides food delivery services to enhance customers' emotional value and price value, as customer loyalty is mainly influenced by the platform's ability to connect the users and service providers at a reasonable/economical price. The study contributes to the development of the theory by testing the robustness of the impact of platform values on customer loyalty using the service-dominant logic.
Keywords: 650; Value co-creation; value proposition; value-capture mechanism; loyalty; sharing economy